2020
DOI: 10.14336/ad.2020.0301
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Infusion Shows Promise for Combating Coronavirus (COVID-19)- Induced Pneumonia

Abstract: A new study published by the journal Aging & Disease reported that intravenous administration of clinical-grade human mesenchymal stem cells (MSCs) into patients with coronavirus disease 2019 (COVID-19) resulted in improved functional outcomes (Leng et al., Aging Dis , 11:216-228, 2020). This study demonstrated that intravenous infusion of MSCs is a safe and effective approach for treating patients with COVID-19 pneumonia, including elderly patients displaying severe pneumonia. COVID-19 is a severe acute respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 21 publications
0
121
0
2
Order By: Relevance
“…Starting by this preliminary, but fundamental work, it is necessary to specify that, as reported in the study of Leng et al [1], and as confirmed by accompanying editorial work by Shetty e al [16], the MSCs used are a certified cellular product.…”
Section: Preliminary Results Of Mesenchymal Stem Cells (Mscs) Infusiomentioning
confidence: 99%
See 4 more Smart Citations
“…Starting by this preliminary, but fundamental work, it is necessary to specify that, as reported in the study of Leng et al [1], and as confirmed by accompanying editorial work by Shetty e al [16], the MSCs used are a certified cellular product.…”
Section: Preliminary Results Of Mesenchymal Stem Cells (Mscs) Infusiomentioning
confidence: 99%
“…No acute infusion-related or allergic reactions were observed after transplantation [1,16]. Similarly, no delayed hypersensitivity or secondary infections were detected after treatment [1,16].…”
Section: Potential Use Of Adipose-derived Stromal Stem Cells (Ascs) Amentioning
confidence: 94%
See 3 more Smart Citations